ERTUGLIFLOZIN MITIGATES LIVER DAMAGE DURING SEPSIS: EVIDENCE FROM A MURINE MODEL - ALRUFAIE, SALSABEEL H.; JANABI, ALI M. (International Journal of Applied Pharmaceutics, 2026)
Objective: This study sought to examine the liver-protective effects of ertugliflozin in male mice subjected to CLP-induced sepsis. Methods: Overall, 24 male albino Swiss mice, aged eight to twelve weeks and weighing 25–35 g, were segregated into four separate groups (n=6 each): the Sham, CLP, CLP+DMSO, and CLP+ertugliflozin groups. In the sham group, the mice were anaesthetized and subjected to laparotomy without cecal ligation and puncture (CLP), whereas in the sepsis group, the mice underwent CLP. The CLP+DMSO group received DMSO (the vehicle for ertugliflozin) through intraperitoneal injection one hour before CLP. In the CLP+ertugliflozin group, 20 mg/kg was administered via the intraperitoneal method one hour before CLP. Biochemical indicators (GPT, GOT, IL-6, TNFα, MDA, GSH, Bax, pERK1/2, and caspase-3) and histological changes were assessed. Results: ELISA was used to investigate the levels of the study parameters in hepatic tissues. Compared with those in the sham group, the levels of TNFα, IL6, Bax, caspase3, MDA and phospho-ERK1/2 were significantly elevated in the mice subjected to sepsis via caecal ligation and puncture (CLP), whereas the GSH level was significantly decreased. In contrast, treatment of septic mice with ertugliflozin significantly reduced these parameters in comparison with those of the sepsis group. Furthermore, histopathological examination revealed that the occurrence of sepsis via CLP resulted in significant liver damage compared with that in the sham group. Conversely, the treatment of mice subjected to CLP with ertugliflozin significantly mitigated liver injury. Conclusion: Ertugliflozin, which inhibits SGLT2, has significant hepatoprotective effects on CLP-induced sepsis, mainly via its antioxidant, anti-inflammatory, and antiapoptotic effects.